Does Rivaroxaban Better than Vitamin K Antagonists in Atrial Fibrillation Patients Undergoing PCI? - Maamar Kara; Omar Aitmokhtar; Adel Azaza; Saber Seddiki; Faiza Harbi; Arezki Sik; Kheireddine Merad; Salim Benkhedda (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2016)
ACS: Acute Coronary Syndrome; AF: Atrial Fibrillation; DAPT: Dual Antiplatelet Therapy; INR: InternationalNormalized Ratio; MI: Myocardial Infarction; PCI: Percutaneous Coronary Intervention; PIONEER AF-PCI: Open-Label, Randomized, Controlled, Multicenterstudy Exploring two Treatment Strategiesof Rivaroxaban and a Dose-Adjusted Oral Vitamink Antagonist Treatment Strategy in Subjectswith Atrial Fibrillation Who Undergo Percutaneous Coronary Intervention; TIMI: Thrombolysis In Myocardial Infarction; VKA: Vitamin K Antagonist Approximately 15% of AF patients have a history of myocardial infarction. Between 5-15% of them will require stenting at some point in their lives with the need for a triple therapy combining an oral anticoagulant, a P2Y12 Inhibitor and aspirin [1-3]. This combination requires careful evaluation of bleeding risk, stroke risk and the risk of acute coronary syndromes (ACS) to reduce the risk of major hemorrhage [4-6]. In this context, the PIONEER AF-PCI [7], trial was conducted to evaluate the effectiveness and safety of anticoagulation with rivaroxaban plus either one or two antiplatelet agents.